The meaning of death attributed by protestants and neo-pentecostals - Pinezi, Ana Keila Mosca (Paidéia (Ribeirão Preto), 2009)
This article aims to understand and interpret the meaning two different protestant groups, located in Ribeirão Preto-SP, Brazil, attribute to death. One is the International Church of the Grace of God, a neopentecostal church and a traditional one, presbyterian. Ethnography was employed during the services and meetings of both churches in addition to open-ended interviews with participant observation. Collected data were compared. Results revealed that the presbyterians' concept of hope is linked to meeting again in heaven and victory over death through eternal life and the second coming of Jesus Christ. Death for them is denaturalized and ritualistic. In contrast, neopentecostals view death as a natural rupture of life and do not ritualize it in the sacred space. In their view, death is opposed to the endless search for divine blessings, especially material ones and those related to healing the body.